2012
DOI: 10.1007/s12350-012-9585-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic value of exercise technetium-99m tetrofosmin myocardial perfusion single-photon emission computed tomography

Abstract: BackgroundExercise 99mTc-tetrofosmin single-photon emission computed tomography (SPECT) is a useful tool for short- and medium-term risk stratifications. Currently, the long-term prognostic application of this technique has not been evaluated.Methods and ResultsExercise 99mTc-tetrofosmin was performed in 655 consecutive patients. Ten patients who underwent revascularization <60 days after nuclear testing were excluded from the analysis. The present data are based on 638 patients with complete follow-up. An abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Normal MPI was defined on the basis of perfusion as SSS of 0-3. 22 Perfusion abnormalities were further categorized on the basis of SSS into mild (4)(5)(6)(7)(8), moderate (9-13), or severe (>13). 22 Reversible perfusion abnormalities, signifying stress-induced myocardial ischemia, were defined as SDS ≥2 and further categorized on the basis of SDS as mild (2-4), moderate (5-7), or severe (>7).…”
Section: Stress Mpimentioning
confidence: 99%
See 1 more Smart Citation
“…Normal MPI was defined on the basis of perfusion as SSS of 0-3. 22 Perfusion abnormalities were further categorized on the basis of SSS into mild (4)(5)(6)(7)(8), moderate (9-13), or severe (>13). 22 Reversible perfusion abnormalities, signifying stress-induced myocardial ischemia, were defined as SDS ≥2 and further categorized on the basis of SDS as mild (2-4), moderate (5-7), or severe (>7).…”
Section: Stress Mpimentioning
confidence: 99%
“…[1][2][3][4][5][6] Numerous studies have demonstrated that abnormal MPI predicts a multifold increase in the risk of major adverse cardiac events (MACE). [1][2][3][4][5][6] Furthermore, the prognostic utility of MPI is incremental to clinical, treadmill stress test, and coronary angiography data. [7][8][9] The robust prognostic data, favorable diagnostic performance, and wide availability of SPECT-MPI have led to a great expansion in use with consequent excessive expenditure.…”
mentioning
confidence: 99%
“…25,38 In the European context, reported followup periods were 10, 11, and 15 years, respectively, in only 47, 294, and 233 patients with normal MPS, 14,15,35 However, in small, low-risk populations a consequently low overall event rate precludes differentiation of risk. 39 The strengths of the present study are the large population, the completeness of follow-up, and a follow-up period sufficiently long to allow for the prognostic importance of underlying risk factors to become unmasked with the opportunity of bringing new aspects to changes in risk over time.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…12,13 Recently, reports on long-term outcome after (normal) MPS have also been emerging. 14,15 Despite this wealth of information, gaps in our knowledge base do still remain. 11,16 These knowledge gaps concern long-term outcome, in some cases revealing shifts in risk over time, thus refining our knowledge on prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Numerous studies have demonstrated that patients with normal MPI have an annual risk of major adverse cardiovascular events (MACE) of less than 1%, while an abnormal MPI scan predicts a multifold increase in risk. [2][3][4][5][6] Multiple studies demonstrated that the prognostic utility of MPI is incremental to clinical data, exercise treadmill test, and coronary angiography. [7][8][9] In addition, MACE risk can be further defined by severity, size, and reversibility of perfusion abnormalities.…”
Section: Introductionmentioning
confidence: 99%